2016
DOI: 10.1080/08958378.2016.1246628
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of electronic-cigarette exposure generation system (Ecig-EGS) for the physico-chemical and toxicological assessment of electronic cigarette emissions

Abstract: Electronic cigarettes (e-cig) have been introduced as a nicotine replacement therapy and have gained increasing attention and popularity. However, while findings on possible toxicological implications continue to grow, major knowledge gaps on both the complex chemistry of the exposure and toxicity exist, prohibiting public health assessors from assessing risks. Here a versatile electronic cigarette exposure generation system (Ecig-EGS) has been developed and characterized. Ecig-EGS allows generation of real wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 76 publications
2
31
0
1
Order By: Relevance
“…Mice were exposed to ECS (10 mg/mL), 3 h/d, 5 d/wk, for 12 wk. ECS was generated by an E-cig machine, as previously described ( 64 ). An automated three-port E-cigarette aerosol generator (e∼Aerosols) was used to produce E-cigarette aerosols from NJOY top fill tanks (NJOY, Inc.) filled with 1.6 mL of e-juice with 10 mg/mL nicotine in a propylene glycol/vegetable glycerin mixture (50/50 by volume; MtBakerVapor MESA).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were exposed to ECS (10 mg/mL), 3 h/d, 5 d/wk, for 12 wk. ECS was generated by an E-cig machine, as previously described ( 64 ). An automated three-port E-cigarette aerosol generator (e∼Aerosols) was used to produce E-cigarette aerosols from NJOY top fill tanks (NJOY, Inc.) filled with 1.6 mL of e-juice with 10 mg/mL nicotine in a propylene glycol/vegetable glycerin mixture (50/50 by volume; MtBakerVapor MESA).…”
Section: Methodsmentioning
confidence: 99%
“…Our assessment of the e-cigarette aerosol both with and without nicotine had similarly elevated levels of PM compared with FA. Several studies have reported the presence of fine and ultra-fine PM in e-cigarette aerosols (Ingebrethsen et al 2012;Melstrom et al 2017;Zhao et al 2016), as well as carbonyls, volatile organic compounds, and metals (Cheng 2014; Wagner et al 2018). Although we were not able to specifically define the PM composition generated from the e-cigarette aerosols in this study, a previous report from our laboratories demonstrated behavioral alterations in response to maternal PM 2:5 exposure (Church et al 2018).…”
Section: Comparison With Human E-cigarette Use and Study Limitationsmentioning
confidence: 99%
“…Electronic (e-) cigarettes are battery-powered devices that generate and deliver vaporized nicotine, fl avorings, and other additives ( Figure 1). The variety of e-cigarettes available in the current market can be categorized into three broad types: a disposable cigarette-like device, a vape pen with a disposable tank, and an advanced personal vaporizer with a refi llable tank (Zhao, Pyrgiotakis, & Demokritou, 2016). These products have been endorsed as alternatives to tobacco smoke and advertised as smoking cessation aids.…”
Section: Introductionmentioning
confidence: 99%